Rosacea as a disease of modern times - epidemiology, recognition - Chudek, Ewelina; Urtnowska-Joppek, Katarzyna (Journal of Education, Health and Sport, 2018)
The purpose of this work is to present the clinical picture and epidemiology of the disease which is rosacea. Factors causing the disease, dermatological criteria for its diagnosis as well as the development stages of the disease are also taken into account. Rosacea is a chronic and very difficult disease to treat as well as in the care therapy. Patients suffering from this condition must follow a restrictive diet and change their habits, as well as give up addictions. An important aspect of the treatment and care of the skin covered by rosacea is self-discipline and adherence to dermatological recommendations and cosmetology. Physiotherapeutic and cosmetological treatments that can warm up a given disease area - mainly massages and hot wraps - are strictly forbidden.